Biology and Culture of a Tropical Harpacticoid Copepod, Nitocra Affinis Californica Lang - Matias-Peralta, Hazel Monica (2004)
The complete post-embryonic development of Nitocra affinis was studied on specimens cultured under normal laboratory conditions (30ºC and 12:12hours L:D cycle). Egg sac is produced 1-2 days (0.95±0.08 days) following a successful insemination. Female produced an average of 7.0±0.0 broods, minimum of 6.0±0.0 and a maximum of 8.0±0.0. The average number of eggs per sac was 18.3±0.25 (ranges from 12-25 eggs per sac). The egg sacs were carried for 18-29 hours or 22.8±2.0 hours on average. Development of nauplii (stages NI through NVI) is completed within 4-5 days (4.66±0.06 days) while copepodid development (stages CI through CVI) occurred within 5-7 days (6.21±0.15 days). The total generation time (egg to adult) was 9-12 days (10.91±0.18 days). Body length of nauplii ranged from 65.4±0.6 µm (NI) to 214.1±2.8 µm (NVI) while copepodid ranged from 235.2±2.9 µm (CI) to 389.6±7.2 µm (CVI or adult). 0Usin0g different food items (three different algal species; Chaetoceros calcitrans, Nannochloropsis oculata and Tetraselmis tetrathele and their combinations; and three artificial food; baker’s yeast, shrimp feed and rice bran) and feeding densities (104, 105, 106 and 107 cells/ml for algal food and 0.02, 0.04 and 0.06 mg/ml for artificial food), the growth and development of N. affinis were studied. In both single and combined algal food, the highest (p<0.05) egg and copepod production/female was achieved using the density 106 cells/ml whereas 0.06 mg/ml was the best (p<0.05) feeding for artificial diet. The highest (p<0.05) fecundity was achieved with copepod fed with mixed algal diet with an average of 18.3±0.3 eggs/sac. The highest (p<0.05) offspring production was achieved with N. affinis fed C. calcitrans (with mean total production reaching a maximum of 132.0±3.8 offspring/female), followed by those fed with mixed (124.8±1.7 offspring/female) and combination of C. calcitrans:T. tetrathele (113.0±1.3 offspring/female). Likewise the highest (p<0.05) survival from nauplii to adult (97-98%) and highest (p<0.05) maximum specific growth rate (K=0.43±0.0) was achieved by copepod fed algal food C. calcitrans, and all its combinations. The shortest (p<0.05) time for egg maturation and time interval between egg sac was found in the T. tetrathele fed copepod. Likewise the shortest (p<0.05) development time from nauplii to copepodid and copepodid to adult resulted from feeding with T. tetrathele.